Lectotypification of the name Actinotinus sinensis (Adoxaceae) - Deng, Yunfei; Liu, Jun (Phytotaxa, 2023)
The specimen, Henry 4058, the type of Actinotinus sinensis was found through the trick prepared by one of Henry’s collectors who has artfully inserted an inflorescence of Viburnum into the terminal bud of an Aesculus. According to the Code operating prior to 1975, the name Actinotinus and A. sinensis must be abandoned, but they may be available for use under the current Code. The application of the names Actinotinus and A. sinensis are confusable. To clarify the confused situation, the part of inflorescence and flowers is chosen as the lectotype for the name A. sinensis for the purpose of maintaining the nomenclatural stability.